Laparoscopic specimen retrieval and attitudes towards morcellation: a questionnaire survey of gynaecology consultants in the United Kingdom. (3rd April 2019) - Sankaran, Sridevi; Brown, Anna; Kent, Andrew; Odejinmi, Funlayo
Abstract: The aim of this study was to evaluate the practices of laparoscopic specimen retrieval among Gynaecologists in the United Kingdom and to determine any variation in practice. A survey of Consultant Gynaecologist members of the British Society of Gynaecological Endoscopy (BSGE) was conducted using Survey Monkey™. Of the 460 registered consultants, 187 (40%) responded to the questionnaire. Sixty-two percent (62%) of the respondents considered themselves to be advanced laparoscopic surgeons whilst 34% considered themselves to be intermediate laparoscopic surgeons. The umbilical port was the most commonly used port for specimen retrieval and it was used to remove 49% of ectopic pregnancies, 43% of ovarian cysts and 43% of endometrioma. Most respondents would not insert an extra port or extend the existing port just for the retrieval of a specimen. The level of laparoscopic experience and the gender did not affect the method of specimen retrieval in cases of ectopic pregnancies, endometrioma and ovarian cysts ( p value >.05, not significant). The majority of respondents used power morcellation for a laparoscopic myomectomy (85% of respondents) and laparoscopic subtotal hysterectomy (93% of respondents), despite the recent concerns surrounding power morcellation. Impact statement: What is already known on this subject? There is a paucity of literature regarding laparoscopic specimen retrieval in gynaecology. In view of recent controversy pertaining to the potential upstaging of leiomyosarcoma with morcellation, other methods of specimen retrieval are gaining an importance. What do the results of this study add? This study shows that the umbilical port is the most commonly used port for specimen retrieval among UK gynaecologists and that most gynaecologists would not insert an additional port purely for specimen retrieval. Most respondents would still use power morcellation for a laparoscopic myomectomy and subtotal hysterectomy, despite the recent concerns over morcellation and its safety. What are the implications of these findings for clinical practice and/or further research? This paper demonstrates the need for development of a database of morcellation practices to enable analysis of both benefits and potential adverse outcomes. This paper will also encourage future research and the audit of specimen retrieval.